15th MEDITERRANEAN RHEUMATOLOGY CONGRESS (ISTANBUL, TURKEY, 28–31 AUGUST 2014) - N. V. Seredavkina; L. N. Denisov; T. V. Korotaeva; L. V. Kondratyeva; M. V. Podryadnova (Научно-практическая ревматология, 2015)
The paper presents a brief review of the proceedings of the 15th Mediterranean Rheumatology Congress that was held in Istanbul, Turkey, in August 2014. This congress unites the scientists and physicians of Mediterranean countries and focuses the attention of rheumatologists and allied health professionals on the geographical and ethnical features of the pattern of human diseases caused by the inflammatory and metabolic involvement of the locomotor apparatus, as well as the peculiarity of the course of rheumatic diseases and treatment response. The goal of the congress is not only to present information on the latest advances in rheumatology, but also to create conditions for the academic exchange of knowledge at an international level and for the promotion of new investigations.